Energy Intake Deficiency Promotes Bone Resorption and Energy Metabolism Suppression in Japanese Male Endurance Runners: A Pilot Study. Issue 1 (February 2020) - Taguchi, Motoko; Moto, Kuniko; Lee, Sihyung; Torii, Suguru; Hongu, Nobuko
It has been reported that male athletes face increased risk for low energy availability and resulting health consequences similar to female athletes. The present study aimed to reveal the energy status of Japanese male runners and to examine the association between energy deficiency and physiological characteristics such as energy metabolism, bone health, and hormonal status. Six male collegiate long-distance runners during a training season participated in this study. Energy intake (EI) was assessed using 3-day dietary records with food pictures. Exercise energy expenditure (EEE) was determined by the HR-VO2 method. Body composition and bone status were measured by dual-energy X-ray absorptiometry. Energy availability (EA) was calculated by subtraction of EEE from EI and normalized by fat-free mass (FFM). Energy balance (EB) was calculated EI minus estimated total energy expenditure (TEE). Resting energy expenditure (REE) was measured by indirect calorimetry using the Douglas bag technique, and blood sampling was conducted to assess hormonal status. The mean EA of the subjects was 18.9 ± 6.8 kcal/kg FFM/day, and severe negative EB (range: −1444 ~ −722 kcal/d) was observed. REE of four runners was suppressed, and moreover, bone resorption was promoted in all subjects. The data in our study suggested that energy deficiency could promote bone resorption and energy metabolism suppression in Japanese male endurance runners. Additional short- and long-term studies are needed to clarify the health risks caused by energy deficiency in male athletes and explore strategies to prevent health problems related to energy deficiency in long-distance runners.